Comparative Analysis of CPU Performance on FreeBSD 64-bit and RedHat 64-bit Operating System Against Denial of Service (DoS) Using Hping3 - Ihsan Fadli Tampati; Faizal Gani Setyawan; Wiyar Wilujengning Sejati; Aqwam Rosadi Kardian (Universitas Negeri Medan, 2023)
Denial of Services (Dos) attack is a type of attack against server traffic. DoS works by placing a heavy load on the server, so that the server cannot accommodate connections from other users and can cause system failure on the server. On the other hand, Denial of Services (DoS) attacks can be used to test server resilience. The servers to be tested are using RedHat Linux and FreeBSD operating systems. Testing is carried out by flooding the system with DoS attacks using the hping3 tool, then comparing the test results in the form of percentages of CPU consumption and memory consumption between operating systems to determine vulnerabilities in each operating system. Based on a comparison of test results between operating systems, the FreeBSD operating system has better CPU performance than the RedHat Linux operating system, but has a vulnerability in internal memory to DoS attacks. Meanwhile, the RedHat Linux operating system has better internal memory performance than the FreeBSD operating system, but has a vulnerability in CPU performance against DoS attacks.